Research on the innate immune response in transgenic mice following ischemic stroke - Yuan, Chao; Shentu, Yuting; Ji, Qiuhong (Frontiers in Aging Neuroscience, 2024)
The high incidence, death, disability, and recurrence of ischemic stroke (CIS) place a significant cost on families and society. According to recent research on the condition, immune-related damage is a major contributor to the development and occurrence of CIS. Innate immunity and adaptive immunity are the two primary categories of the immune system in the body. The body’s first line of defense is innate immunity, and immune cells play a role in every stage of the immune system. At the same time, protein molecules play a vital function in regulating and differentiating immune cells. It can be said that protein molecules are the foundation of immune regulation. Model mice are necessary for us to examine fixed compounds in our studies. Conditional deletion and overexpression mouse models are the two primary categories of model mice. Numerous model mice have been documented in CIS research. The study of innate immune responses following ischemic stroke will benefit more from the use of these transgenic mice that target innate immunity. This paper analyzes the literature on transgenic mice related to innate immune responses following ischemic stroke because of the significance of these responses. It is anticipated to produce novel medications, improve clinical treatment guidance, and undergo a metamorphosis and application in the clinic in the future.